Magnetic substrate supported ZnO-CuO nanocomposite as reusable photo catalyst for the degradation of organic dye. (2017) - Shivaramu, Prasanna D.; Patil, Asha; Murthy, M.; Tubaki, Suresh; Shastri, Mahesh; Manjunath, S.; Gangaraju, Vinay; Rangappa, Dinesh
Abstract: Magnetic substrate supported heterogeneous nanocatalysts are emerging materials in the field of catalysis. In the present study, magnetic iron oxide supported zinc oxide – copper oxide nanoparticles were synthesised, characterised and evaluated for their photo catalytic activity. Iron oxide nanoparticles were synthesised by simple chemical co-precipitation method and coated with silica by conventional Stober's method then the surface was decorated with with ZnO-CuO nanocomposite. The obtained nanocomposite was characterised by X-ray diffraction (XRD), Fourier transform infrared spectroscopy(FTIR), Scanning Electron Microscopy (SEM) and Energy-Dispersive Spectra (EDS). The XRD results confirmed the spinal crystal structure of Fe3 O4 and well matches with the peaks of ZnO and CuO. FTIR peak at 1090 cm -1 confirmed the presence of Si and peaks below 1000 cm -1 confirmed the presence of metals like Fe, Zn and Cu. SEM results confirmed the spherical and cubic mixed morphology of the nanocomposite. EDAX confirmed the presence of all the elements with high purity. Photocatalytic activity of the nanocomposite was evaluated for degradation of Indigo carmine(IC) dye under UV-visible light irradiation. Indigo Carmine dye was degraded within 2 hrs. The catalyst was easily recovered by applying external magnetic and reused couple of times.